SINTESIS DAN KARAKTERISASI ZEOLIT-TiO2 SERTA PEMANFAATANNYA SEBAGAI FOTOKATALIS UNTUK DEGRADASI RHODAMIN B - Fauzi, W. A.; Simpen, I N.; Sudiarta, I W. (Jurnal Kimia (Journal of Chemistry); Vol.13 No.1 Januari 2019DO - 10.24843/JCHEM.2019.v13.i01.p12, 2019)
The synthesis of zeolite-TiO 2 composite has been successfully performed by mixing the H 2 SO 4 -enriched natural zeolite to TiO 2 . The composites are formed then characterized functional groups using Fourier Transform Infrared (FTIR) and surface area with BET (Breunaur, Emmet and Teller) method. The characterization results showed that the synthesis of zeolite-TiO 2 composites is relatively successful. Those can be seen from BET characterization higher to the composite surface area from 63.031 m 2 /g to 73.913 m 2 /g, then reinforced by the appearance of the functional groups of TiO 2 in zeolite at wavelength 2345.44 cm -1 , 792.74 cm -1 and 424.34 cm -1 . Furthermore, the composite is used for the photodegradation of rhodamin B dyes with the highest degradation percentage was 97.39% in optimal irradiation contact time was reached at 10 minutes and the effective pH of 4